Assessment on Vietnam's Transport Infrastructure Development Investment under the mode of Public-Private Partnership - Proposing Solutions - Le Manh Tuong,; Le Hoai Linh,; Dang Hoang Tuan,; Le Phi Vu, (International Journal of Scientific Research in Civil Engineering, 2021)
The goal of developing the country's infrastructure system, especially for underdeveloped or moderately developed countries such as Vietnam is extremely important. To become a modern industrialized country, not only Vietnam but any other countries are required to have an appropriate policy mechanism to strengthen infrastructure, attracting private investment, capital sources while public investment capital remained limited.Solutions to attract investment in infrastructure development in general and transport infrastructure in particular are expected to include perfecting laws, mechanisms and policies, management model. Those will create favorable conditions for domestic and foreign economic sectors to participate in many forms, especially completing the investment under the PPP (Public-Private partnership) model in line with international practices.After nearly 15 years of implementing PPP investment in the construction of transport infrastructure, Vietnam has initially achieved certain results, contributing to the expansion and upgrading of its current transport infrastructure system. Besides public investment capital, government bond capital, official development assistance (ODA), there are sources of investment capital from the non-state sector through PPP project contracts (mainly BOT and BT ones) which have significantly changed the transport infrastructure system in Vietnam (completion of nearly 3,000-km roads of all kinds). In the period of 2021-2025, Vietnam is projected to complete 5,000 km of expressways, in order to create a major economic breakthrough. In the context of limited public investment capital, the PPP investment form is considered the most feasible.
Keywords: Public-private Partnership (PPP); Investment Management; Investment Attraction; Road Transport Infrastructure